Determination of the corrosion rate inside historical brass wind instruments – Proof of concept. Issue 12 (8th May 2016) - Elsener, B.; Cocco, F.; Fantauzzi, M.; Palomba, S.; Rossi, A.
Abstract : An electrochemical sensor has been tested on brass reference samples and applied on a mouthpiece of a historical brass instrument. Using a phosphate buffer solution pH 7 with 10 −2, 10 −3 and 10 −4  M NaCl, the electrochemical response (open circuit potential, polarisation resistance) of the sensor corresponds to the results obtained in a traditional electrochemical cell. XPS surface analysis has shown that the brass surface composition after 7 min contact with the sensor is not altered when using 10 −3 or 10 −4  M NaCl. The sensor is fit for purpose and has already been applied in brass wind instruments. Abstract : An electrochemical sensor has been developed. XPS analysis after the use of the sensor on model brass alloys showed no alteration of the surface. The sensor can assess the instantaneous corrosion rate inside historical brass wind instruments that are increasingly used for concerts. This allows the conservator to judge the risk of damages and test the efficiency of preventative measures.